Análise da prática docente em uma organização pública de ensino superior após a implementação do programa Reuni: uma análise da sua gestão por meio da teoria da atividade - Barreto, Sheila Cristina da Silva Góes (2017)
Understanding to be the teaching practice as an organized activity with historical occurrences, in a continuous process of creating and re-creating, which is continuously developed, this thesis aims at the analysis of this practice after the implementation of the Support Program for Expansion and Restructuring Plans of the Federal Universities - Reuni, in the light of the Theory of Activity - TA. The use of TA was justified by the fact that the Theory allows an analysis of the process of change through historicity, multiplicity of voices and use of mediating tools. The teaching practice was understood as a social activity, historically situated, intermediated by four Systems of Activity: Teaching, Research, Extension and Management - potentially sharing the object Reuni. Through an exploratory research, a historical survey of the Plans of Expansion of the Brazilian Universities was made, identifying the demands related to the teaching practice, resulting from these plans. The study involved the interpretation of the interaction processes for the understanding of the phenomenon, from a social and historical point of view, with evidences collected in the documentary analysis and individual and collective interviews. The Activity Systems were analyzed based on data prior to and after the implementation of the Reuni, allowing the elaboration of a comparative of the teaching practice in UFPR, in two historical moments. It was analyzed that the discussion that preceded the adhesion to Reuni was not done in a broad way, nor with the participation of the academic community. It occurred under questions and concerns of teachers. It was also observed that the working conditions of teachers in higher education were determined by a historical-social context linked to quantitative goals. Complementarily, the precariousness of its practice occurred through educational policies and reforms that occurred over time, in addition to the pressures of the metrics system, associated with the changes in the world of activities experienced by teachers.